The effect of constant-intensity endurance training and high-intensity interval training on aerobic and anaerobic parameters in youth - Runacres, A.; Mackintosh, K. A.; McNarry, M. A. (Journal of Sports Sciences, 2019)
Introduction: High-Intensity Interval Training (HIIT) and Constant-Intensity Endurance Training (CIET) improves peak oxygen uptake (V.O2) similarly in adults; but in children this remains unclear, as does the influence of maturity. Methods: Thirty-seven boys formed three groups: HIIT (football; n = 14; 14.3 ± 3.1 years), CIET (distance runners; n = 12; 13.1 ± 2.5 years) and a control (CON) group (n = 11; 13.7 ± 3.2 years). Peak V.O2 and gas exchange threshold (GET) were determined from a ramp test and anaerobic performance using a 30 m sprint pre-and-post a three-month training cycle. Results: The HIIT groups peak V.O2 was significantly higher than the CON group pre (peak V.O2: 2.54 ± 0.63 l/min vs 2.03 ± 0.53 l/min, d = 0.88; GET: 1.41 ± 0.26 l/min vs 1.13 ± 0.29 l·min-1, d = 1.02) and post-training (peak V.O2: 2.63 ± 0.73 l/min vs 2.08 ± 0.64 l/min, d = 0.80; GET: 1.32 ± 0.33 l/min vs 1.15 ± 0.38 l/min, d = 0.48). All groups showed a similar magnitude of change during the training (p > 0.05). Conclusion: HIIT was not superior to CIET for improving aerobic or anaerobic parameters in adolescents. Secondly, pre- and post-pubertal participants demonstrated similar trainability.